Temperature-Programmed Reduction and Dispersive X-Ray Absorption Spectroscopy Studies of CeO2-Based Nanopowders for Intermediate-Temperature Solid-Oxide Fuel Cell Anodes - Bellora, Marina Soledad; Sacanell, Joaquín; Huck Iriart, Cristián; Soldati, Analía Leticia; Larrondo, Susana Adelina; Lamas, Diego Germán (Scientific Research Publishig, 2019)
Fil: Bellora, Marina Soledad. Comisión Nacional de Energía Atómica; Argentina. Universidad Nacional de San Martín. Escuela de Ciencia y Tecnología; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina